2004
DOI: 10.1242/jcs.00986
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microtubules, cell polarity and adhesion in electric-field-mediated motility of 3T3 fibroblasts

Abstract: Direct-current electric fields mediate motility (galvanotaxis) of many cell types. In 3T3 fibroblasts, electric fields increased the proportion, speed and cathodal directionality of motile cells. Analogous to fibroblasts' spontaneous migration, we initially hypothesized that reorientation of microtubule components modulates galvanotaxis. However, cells with intact microtubules did not reorient them in the field and cells without microtubules still migrated, albeit slowly, thus disproving the hypothesis. We nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
68
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 78 publications
12
68
0
1
Order By: Relevance
“…Cells grown on flat, non-grooved surfaces were exposed to an EF of 200mV/mm, From the cell population (n=339), 84% of cells aligned perpendicular, at angles of >800, to the EF vector, in agreement with other studies [6][7][8]. Figure 2 summarises these difference in cell alignment between cells exposed to grooves only (depth of 347 nm and width of 2 1m) and EFs only.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Cells grown on flat, non-grooved surfaces were exposed to an EF of 200mV/mm, From the cell population (n=339), 84% of cells aligned perpendicular, at angles of >800, to the EF vector, in agreement with other studies [6][7][8]. Figure 2 summarises these difference in cell alignment between cells exposed to grooves only (depth of 347 nm and width of 2 1m) and EFs only.…”
Section: Resultssupporting
confidence: 83%
“…Another physiologically relevant guidance cue is an electric field (EF), which is present in many tissues during development and wound repair [5]. Fibroblasts respond to a d.c. EF by aligning their long axes perpendicular to the direction of the EF vector [6][7][8], and migrating towards the cathode [6,7], although a recent study showed that EFs do not direct the migration of fibroblast cells cultured on collagen I [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, microtubules are also known to regulate other aspects of cell behavior including cell polarization (Finkelstein, 2004;Sloboda, 1980;Watanabe, 2005). In order to assess these Rho kinase independent functions in corneal fibroblasts, we studied the effects of microtubule disruption in the presence of the specific Rho-kinase inhibitor Y-27632.…”
Section: Microtubules Regulate Cell Polarization and Morphology In 3-mentioning
confidence: 99%
“…Several cell types that are implicated in wound repair increase their speed and direction of migration (electrotaxis) in response to an EF, as summarized in Table 1. 14,[19][20][21][22][23][24][25][26][27][28][29][30] Along with the antibacterial effect that EFs have shown in several studies, 3 cells involved in the immune response such as neutrophils, lymphocytes, and monocytes show cathodal migration (toward the wound center) in an EF. 14,19 Granulocytes migrate toward the anode at 2.5 mM Ca 2 + and toward the cathode at 0.1 mM Ca 2 + .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that fibroblasts can show both cathodal and anodal electrotactic responses. 14,23,[27][28][29][30] Additional studies on animal models and in cell cultures of dermal fibroblasts stimulated with a direct current (DC) EF demonstrated a significant increase in the ability of fibroblasts to synthesize collagen, produce DNA, and synthesize protein. In addition, the speed of epithelialization in the wound was noticeably increased.…”
Section: Discussionmentioning
confidence: 99%